Métricas de marketing para ações de relacionamento no varejo - estudo de caso - Azevedo, Liduina Ribeiro de (2011)
The growing importance of marketing activities and increased investments in the area justify the charge carried by senior management to evaluate and measure the results of marketing. This dissertation aims to check the application of marketing metrics proposed by Farris et al (2007), on the book Marketing Metrics, use on measuring marketing relationship actions results. In order to that, an exploratory study based on approaches and definitions of marketing relationship and its metrics was made. The method used was a case study in a Fortaleza supermarket network, which data to calculate the metrics were obtained by questionnaire. The analysis indicates that the metrics are relevant in measuring the results of the actions on marketing relationship, and that performance measurement is necessary to increase strategies alignment, increasing the credibility of the area on the vision of companies managements.